Lama Simpan Telur Puyuh yang di Rendan dalam Ektrak Etanol Kulit Manggis (Garcia Mangostana L ) : Long Store Quail Eggs in Mangosteen Peel Ethanol Extract (Garcia Mangostana L) - Wicaksono, Putra Bangun; Rinawidiastuti, Rinawidiastuti; Nilamcaya, Mus (Jurnal Riset Agribisnis dan Peternakan, 2024)
Mangosteen was a tannin-containing ingredient that was used as a tanner. The purpose of the study was to determine the effect of mangosteen ethanol extract levels on the shelf life of duck eggs. This study used a factorial pattern RAL, namely the level of ethanol extract of mangosteen peel and storage time. The results of the anova analysis showed that soaking with the level of mangosteen peel extract had a very real effect on the white index value. The results of the anova analysis showed that soaking with the level of mangosteen peel extract had a real effect on the value of the duck egg yolk index. The average results of the egg yolk index treatment had an average value of 0.31-0.36. Soaking the level of mangosteen peel extract gives a noticeable difference in the color of the duck egg yolk. The color of the yolk of duck eggs ranges from 13.95-14.23. The level of mangosteen peel ethanol extract did not differ significantly and the storage time had a very real effect on the pH of duck egg yolk. The level of ethanol extract of mangosteen peel and storage time had a real effect on the pH of duck egg yolk. The conclusion was that the level of mangosteen peel ethanol extract affects the egg white index, yolk index, and does not differ from the color of the yolk, the pH of the egg white, and the pH of the yolk in duck eggs.  The storage time at room temperature affects the egg white index, yolk index, yolk color, pure white pH and was no different from the pH of the yolk in duck eggs.